Efektivitas Metode Sosiodrama Terhadap Hasil Belajar Kognitif dan Minat Belajar Siswa Biologi - Reflianto, Aprianus; Bustami, Yakobus; Syafruddin, Didin (Department of Biology Education, Universitas Pendidikan Indonesia, 2019)
Cognitive learning outcomes and interest in learning are one of the supporting factors in the success of learning. This research aims to determine the results of cognitive learning and interest in learning biology through the implementation of sociodrama method to science students. The approach used in the form of a quantitative approach with the form of quasi-experimental research. The population in this research were all VIII class SMP Negeri 3 Sungai Tebelian consisting of 84 students with a total sample of 42 students. Instruments to measure cognitive learning outcomes in the form of multiple choice questions as many as 20 items, while interest in learning uses a questionnaire sheet of 15 items. Data were analyzed using descriptive statistical analysis to seem the mean value and inferential statistical analysis to seem the hypothesis test using the t-test. The results of the descriptive analysis show that the mean scores of cognitive learning outcomes and learning interest in the experimental and control classes had the same category, which was very lacking while the posttest means of cognitive learning outcomes and interest in learning in the experimental and control classes had different value categories. The experimental class has average cognitive learning outcomes and interest in learning is better than the control class. The results of the inferential statistical analysis show that the significance of cognitive learning outcomes and interest in learning is 0.00 and smaller than 0.05 so that it can be concluded that there are significant differences in cognitive learning outcomes and interest in learning through the implementation of sociodrama method.